Historical and current aspects of angiovisualization methods in CАD (a literature review) - V. O. Hubka; Yu. M. Vaіlo; A. M. Materuhin; A. L. Makarenkov (Zaporožskij Medicinskij Žurnal)
The aim of the work. To summarize and expand knowledge about current methods used for visualization of coronary arteries, their evolution, capabilities, effectiveness, indications for use, safety for patients, guided by the principles of evidence-based medicine.